CAPABILITIES OF COMPUTED TOMOGRAPHY TO EVALUATE POLYMORPHIC CHANGES IN DESTRUCTIVE PANCREATITIS - E. A. Kasatkina; M. Klauss; H.-U. Kauczor; T. V. Riden; T. Hackert; V. E. Sinitsyn; L. Grenacher (Вестник рентгенологии и радиологии, 2016)
Objective: to determine whether the lower-density pancreatic parenchymal areas detected by a computed tomography (CT) study in patients with acute pancreatitis correspond to the necrotic portions of the gland or whether these changes may be reversal.Material and methods. The investigation covered 25 patients who had undergone or dynamic CT studies made at different time intervals. Two independent investigators with 4 and 19 years of experience retrospectively analyzed the results of both CT studies. Target estimation was made of the extent (volume) of and CT density changes in the hypodense areas of the gland parenchyma.Results. Seven (28%) of the 25 patients were noted to have higher CT density in the areas that had decreased density during primary CT studies (more than a 30 HU increase was rated as significant). There was a statistically significant difference between the patient groups when comparing the extent of hypodense areas and the difference in CT density (t-test, p=0.006); Mann–Whitney U-test, p=0.01 for extent difference and t-test, p=0.00; Mann–Whitney U-test, p=0.00 for CT density difference. There was also a correlation between the extent of hypodense areas and the difference in their CT density (Pearson: r=-0.533, p=0.006; Spearman: r=-0.636, p=0.001).Conclusion. The results of our investigation may suggest that the lower-density pancreatic parenchymal areas cannot always correspond to necrotic changes and may be reversible.